2020
DOI: 10.5005/jp-journals-10018-1317
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of COVID-19 Patients at a Medical College Hospital in Bangladesh

Abstract: Background and aim Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has induced a sense of panic around the world as the disease is highly contagious and has been spreading in full swing during last 5 months causing millions of COVID-19 patients and hundreds of thousands of deaths. Bangladesh, a country of 170 million people, is not an exception regarding COVID-19; it has reported several thousand COVID-19 patients with several hundred of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
(13 reference statements)
3
7
0
Order By: Relevance
“…The patients in our study were relatively young with a median age of 31.5 years. This is similar to the data from other South Asian countries [10, 20, 21], but is in contrast to the studies from Italy, UK and USA [13, 14, 19]. This can partly be explained by the fact that the median age of the population in South Asian countries is substantially lower than countries like the US, UK or Italy [22].…”
Section: Discussionsupporting
confidence: 85%
“…The patients in our study were relatively young with a median age of 31.5 years. This is similar to the data from other South Asian countries [10, 20, 21], but is in contrast to the studies from Italy, UK and USA [13, 14, 19]. This can partly be explained by the fact that the median age of the population in South Asian countries is substantially lower than countries like the US, UK or Italy [22].…”
Section: Discussionsupporting
confidence: 85%
“…In our recent case-control study on 37 patients with moderate-to-severe COVID-19 pneumonia, we found that compared to usual daily dose regimen (4 mg) of baricitinib, a single 8 mg oral loading dose-based daily usual dose (4 mg) regimen of baricitinib for 14 days revealed better clinical outcomes, including early normalization of SpO 2 (≥95%) on RA and restoration of normal breathing function [4 (IQR: 4-5)/3 Several studies reported that among the hospital admitted patients with COVID-19, 15.7 to 26.1% cases are severe and often difficult to clinically justify on the basis of abnormal laboratory investigations and CT scan report [16][17][18]. Though, there is no standard antiinflammatory drug therapy for the treatment of severe pneumonia in COVID-19 infection, so early diagnosis and initiation of treatment upon hospital admission with the available drugs may attribute favorable clinical outcome [12,19]. In this study, along with the antiviral and steroid therapy, the anti-inflammatory drug baricitinib was started in both the groups' patients with severe COVID-19 pneumonia within 4 h of hospital admission.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a person having multiple comorbidities who have COVID-19 is at greater mortality risk. NCDs, e.g., heart diseases, hypertension, diabetes, chronic obstructive pulmonary diseases, malnutrition, among others, contribute to COVID-19 in Bangladesh ( Al Mahtab et al, 2020 ). In Bangladesh, 48% of males smoke, which is a significant factor for severe COVID-19 by damaging the lungs severely and affecting other parts of the body ( WHO COVID-19 and NCDs, 2020 ).…”
Section: Covid-19 Morbidity Mortality Scenario and Associated Risk Factors In Bangladeshmentioning
confidence: 99%